Impact of pathologic tumor response in the treatment of gastric cancer - Wong, Joyce (Translational Gastroenterology and Hepatology, 2016)
The treatment of gastric cancer in the U.S. and Europe has largely been affected by trials demonstrating improved survival with perioperative treatment with chemotherapy. As such, assessing the pathologic tumor response to such treatment may provide important information as to the efficacy of neoadjuvant treatment, and several systems have been established to grade the pathologic response. Currently, however, no defined treatment strategy exists for how to treat patients post-operatively with poor tumor response. The question remains: should patients with a poor tumor response to neoadjuvant therapy undergo a different adjuvant therapy strategy?